From semi-starvation to the stage: a case report on indicators of low energy availability in a drug-free bodybuilder during contest preparation and peak week - Alex J. Ritson; Lyle McDonald; Joseph Agu; Laurent G. Bannock (Frontiers in Nutrition)
Natural bodybuilding competitions involve periods of low energy availability (EA) combined with resistance training and high-protein diets to achieve extreme leanness. This study tracked a drug-free bodybuilder adopting evidence-based nutrition practices during 18 weeks of contest preparation. We measured endocrine function, resting energy expenditure, respiratory exchange ratio, body composition, resting heart rate, oral temperature, mood, and strength performance. Endocrine function was remeasured after 2 days of energy repletion. From baseline to week 18, free triiodothyronine (T3) and total testosterone (TT) fell into clinically low (2.7 pmol/L−1) and sub-clinically low (9.1 nmol/L−1) ranges. Resting energy expenditure decreased by −519 kcal (REEratio 0.78), and respiratory exchange ratio decreased from 0.95 to 0.85. Body mass reduced by −5.1 kg, with a sum of eight skinfold loss of −15.7 mm. Correlations were observed between body mass and decreases in oral temperature (r = 0.674, p = 0.002) and resting heart rate (r = 0.560, p = 0.016). Mood remained stable until the final 2 weeks and relative one-repetition maximum decreased in the squat (−5.4%), bench (−2.6%), and deadlift (−3.6%). Following 2 days of modest energy repletion, free T3 increased (18.5%), returning to sub-clinically low values (3.2 pmol/L−1), whereas TT fell (−20.9%), reaching clinically low values (7.2 nmol/L−1). These results offer insight into the dynamics of T3 and TT following a short-term period of modest energy repletion and further information on indicators of low EA during chronic energy restriction.